Analisis Strategi Pengembangan Koperasi LKMS Amanah Berkah Nusantara dengan Pendekatan Matriks Space - Nuriyah, Armida Arka; Rahmadiani, Arzanti; Zuhela, Salma; Shafrani, Yoiz Shofwa (Populer: Jurnal Penelitian Mahasiswa, 2025)
In order to provide financial access to groups in society that are not yet fully served by formal financial institutions, cooperatives have become very important. LKMS Amanah Berkah Nusantara Cooperative is one example of a sharia cooperative, with a non-profit model and a strong social orientation, this cooperative is here to be a solution to financial problems in the business being run. The cooperative needs to be more adaptive in strategizing its development in the face of changes in the current external environment. This research uses the Matrix Space approach, measuring four dimensions, namely financial strength, competitive advantage, industry strength and external environmental stability. As a result, Amanah Berkah Nusantara MFI Cooperative is in an aggressive strategy position as shown through the calculation of space coordinates (X = 4; Y = 0.67), which means that the cooperative has significant strengths in industrial strength and fairly good environmental stability, although it still faces challenges in terms of internal efficiency and technological competitiveness. The most recommended strategy is an active growth strategy that includes regional expansion outside the sub-district, strengthening the inetrnal digitalization system, and differentiating services through intensive assistance to customers